Human breast cancer cells educate macrophages toward the M2 activation status. Issue 1 (December 2015) - Sousa, Sofia; Brion, Régis; Lintunen, Minnamaija; Kronqvist, Pauliina; Sandholm, Jouko; Mönkkönen, Jukka; Kellokumpu-Lehtinen, Pirkko-Liisa; Lauttia, Susanna; Tynninen, Olli; Joensuu, Heikki; Heymann, Dominique; Määttä, Jorma
Abstract Introduction The immune system plays a major role in cancer progression. In solid tumors, 5-40 % of the tumor mass consists of tumor-associated macrophages (TAMs) and there is usually a correlation between the number of TAMs and poor prognosis, depending on the tumor type. TAMs usually resemble M2 macrophages. Unlike M1-macrophages which have pro-inflammatory and anti-cancer functions, M2-macrophages are immunosuppressive, contribute to the matrix-remodeling, and hence favor tumor growth. The role of TAMs is not fully understood in breast cancer progression. Methods Macrophage infiltration (CD68) and activation status (HLA-DRIIα, CD163) were evaluated in a large cohort of human primary breast tumors (562 tissue microarray samples), by immunohistochemistry and scored by automated image analysis algorithms. Survival between groups was compared using the Kaplan-Meier life-table method and a Cox multivariate proportional hazards model. Macrophage education by breast cancer cells was assessed byex vivo differentiation of peripheral blood mononuclear cells (PBMCs) in the presence or absence of breast cancer cell conditioned media (MDA-MB231, MCF-7 or T47D cell lines) and M1 or M2 inducing cytokines (respectively IFN-γ, IL-4 and IL-10). Obtained macrophages were analyzed by flow cytometry (CD14, CD16, CD64, CD86, CD200R and CD163), ELISA (IL-6, IL-8, IL-10, monocyte colony stimulating factor M-CSF) and zymography (matrix metalloproteinase 9, MMP-9). Results Clinically, we found that high numbers of CD163+ M2-macrophages were strongly associated with fast proliferation, poor differentiation, estrogen receptor negativity and histological ductal type (p <0.001) in the studied cohort of human primary breast tumors. We demonstratedex vivo that breast cancer cell-secreted factors modulate macrophage differentiation toward the M2 phenotype. Furthermore, the more aggressive mesenchymal-like cell line MDA-MB231, which secretes high levels of M-CSF, skews macrophages toward the more immunosuppressive M2c subtype. Conclusions This study demonstrates that human breast cancer cells influence macrophage differentiation and that TAM differentiation status correlates with recurrence free survival, thus further emphasizing that TAMs can similarly affect therapy efficacy and patient outcome.